The Influence of Work Stress and Employee Engagement on Job Satisfaction of Civil Servants in the Service Section of UPT Klinik Utama Sungai Bangkong West Kalimantan Province - Usni, Akmal Rachmanda; Mahdi, Irfan (SAINTIS Publishing, 2025)
This study aims to investigate the influence of work stress and employee engagement on job satisfaction among civil servants in the Service Section of UPT Klinik Utama Sungai Bangkong, West Kalimantan Province. A quantitative approach with an associative research method was employed. The population comprised all 89 civil servants working in the Service Section. Given the relatively small population size, a saturated sampling technique was used, meaning the entire population served as the research sample. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that work stress has a negative and statistically significant effect on job satisfaction, whereas employee engagement has a positive and statistically significant effect. Furthermore, the two independent variables jointly have a significant effect on job satisfaction. These results highlight the critical importance of managing occupational stress and fostering employee engagement to enhance job satisfaction and improve the overall effectiveness of public service delivery.